Europe's Place in the Global Economy — What Does the Last Half Century Suggest for the Future? - Mikkel Barslund; Daniel Gros (Intereconomics, 2016)
When Intereconomics was founded 50 years ago, the world was very different. In this contribution, we describe some of the major developments in the global economy and provide an outlook for the medium-term future until 2030. We assess broad demographic trends for major regions of the world, then look at GDP growth and trade, before we turn to human capital and innovation.
Keywords: 330